2020
DOI: 10.2147/copd.s257796
|View full text |Cite
|
Sign up to set email alerts
|

<p>Moderate-to-Severe Obstructive Sleep Apnea and Cognitive Function Impairment in Patients with COPD</p>

Abstract: Prior studies have indicated that patients with chronic obstructive pulmonary disease (COPD) exhibit significant cognitive defects on neuropsychological testing. Obstructive sleep apnea (OSA) is common in patients with COPD and is associated with reduced cognitive function; however, the combined impact of these two conditions on cognitive function is unknown. The aim of the study was to investigate the impact of OSA on cognitive impairment in patients with COPD. Methods: Sixty-five stable COPD patients aged ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…Previous studies showed that the MoCA score was significantly lower and the risk of dementia was dramatically higher in OS patients compared with COPD-only patients. 14 , 19 Additionally, the level of dementia in OS patients was significantly correlated with the severity of OSA. 19 Therefore, it is of great importance to screen cognitive impairment in OS patients at early stage by using appropriate indicators.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies showed that the MoCA score was significantly lower and the risk of dementia was dramatically higher in OS patients compared with COPD-only patients. 14 , 19 Additionally, the level of dementia in OS patients was significantly correlated with the severity of OSA. 19 Therefore, it is of great importance to screen cognitive impairment in OS patients at early stage by using appropriate indicators.…”
Section: Discussionmentioning
confidence: 92%
“… 14 , 19 Additionally, the level of dementia in OS patients was significantly correlated with the severity of OSA. 19 Therefore, it is of great importance to screen cognitive impairment in OS patients at early stage by using appropriate indicators.…”
Section: Discussionmentioning
confidence: 92%
“…About 18% of CI patients experience respiratory dysfunction (Martinez et al, 2014), and 43% of cognitive decline patients have heart failure (HF) (Cannon et al, 2017). Accumulating evidence from different countries not only indicates abnormal cardiopulmonary function increased the risk of cognitive impairment (Emery et al, 2012;Cermakova et al, 2015;Jefferson et al, 2015;Zhang et al, 2020;Duong et al, 2022) but also reveals the complex interactions between cognitive impairment and HRQOL (Ezzati et al, 2019;Liu et al, 2019;Phyo et al, 2021). Currently, the mechanisms of abnormal cardiac function and cognitive impairment mainly involve cerebral hypoperfusion, hypoxia, systemic inflammation, endothelial injury and neurohormonal activation (Cermakova et al, 2015;Diener et al, 2019) and of abnormal pulmonary function and cognitive impairment mainly involved hypoxia, systemic inflammation and cerebral vascular dysfunction (Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Obstructive sleep apnoea (OSA) represents an independent risk factor for adverse cardiac outcomes and impaired cognitive functioning, especially in men ( Zhang et al, 2020 ). Several unfavorable medical conditions have been associated with OSA, for example coronary artery disease (CAD), heart failure, atrial fibrillation, hypertension, stroke ( Goudis and Ketikoglou, 2017 ; Li et al, 2018 ; Salman et al, 2020 ; Roderjan et al, 2022 ), metabolic dysfunction ( Bonsignore et al, 2013 ), and neurocognitive impairment ( Seda and Han, 2020 ).…”
Section: Introductionmentioning
confidence: 99%